PENGARUH KECEPATAN TERHADAP PENINGKATAN KEMAMPUAN LOMPAT JAUH MAHASISWA UNIT KEGIATAN MAHASISWA OLAHRAGA - Alimuddin Alimuddin; Nugroho Susanto (Jurnal Sporta Saintika, 2019)
The long jump sport is not as easy as what we might see on its implementation. This sports branch also has special techniques to do so. Many people have done so, but the results of the expected jumps do not match in reality. The purpose of this research is to know the contributions that are given the physical ability of speed to the student jumping capability of SME sports. The type of research done is simple experimental research. The population of this research is a student of UKM sports. Sampling in this study, authors refer to sampling techniques that are nonprobability of saturated samples. The test is done with a 6-second quick run test. Based on a summary of the results of the descriptive analysis in the table above about the speed data of the UKM sports, it can be described that speed data, of 15 samples were obtained the total value of 712.00. The average value obtained = 47.4667 with the standard deviation result = 6.15127. For the number range = 18.00 is derived from the difference between the minimum value = 40.00 and the maximum value = 58.00 Evident from the results of the analysis (ρ < 0.05) or Ho rejected and H1 accepted, the results were obtained when associated with the skeletal thinking and the underlying theories and basically the results of this research supporting the theory.